2020
DOI: 10.3892/mmr.2020.11011
|View full text |Cite
|
Sign up to set email alerts
|

miR‑296‑3p promotes the proliferation of glioblastoma cells by targeting ICAT

Abstract: Micrornas (mirna/mirs) serve an important function in the regulation of gene expression, and have been indicated to mediate a number of cellular biological processes, including cell proliferation, the cell cycle, cell apoptosis and cell differentiation. The altered expression of mirnas has been revealed to result in a variety of human diseases, including glioblastoma multiforme (GBM). The present study indicated an increase in mir-296-3p in glioma tumor types compared with normal brain, particularly in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that miR‐296‐3p is dysregulated in various tumors, where it can promote or inhibit tumor progression by targeting different genes 18 . For example, miR‐296‐3p has been shown to be upregulated in prostate cancer and glioma and promoted tumor proliferation and metastasis by targeting ICAM‐1 and ICAT, respectively 19,33 . In contrast, miR‐296‐3p has also been reported to function as tumor suppressor and inhibited cell proliferation, metastasis, and drug resistance in lung cancer by targeting PRKCA 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR‐296‐3p is dysregulated in various tumors, where it can promote or inhibit tumor progression by targeting different genes 18 . For example, miR‐296‐3p has been shown to be upregulated in prostate cancer and glioma and promoted tumor proliferation and metastasis by targeting ICAM‐1 and ICAT, respectively 19,33 . In contrast, miR‐296‐3p has also been reported to function as tumor suppressor and inhibited cell proliferation, metastasis, and drug resistance in lung cancer by targeting PRKCA 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that miR‐296‐3p may be regulated by neurofibromatosis 2, and it enhances the invasion capacity of GBM cells via SOCS2/STAT3 (Lee et al, 2016). Similarly, J. Zhou et al (2020) have presented a study indicating an oncogenic role of miR‐296‐3p in glioblastoma via regulating ICAT. With bioinformatics analysis, the target sites of circHECTD1 were detected in the miR‐296‐3p; therefore, we speculated that circHECTD1 may interact with miR‐296‐3p in glioma.…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, J. Zhou et al (2020) have presented a study indicating an oncogenic role of miR-296-3p in glioblastoma via regulating ICAT. With bioinformatics analysis, the target sites of circHECTD1 were detected in the miR-296-3p; therefore, we speculated that circHECTD1 may interact with miR-296-3p in glioma.…”
Section: Introductionmentioning
confidence: 95%
“…More interestingly, the expression of ICAT can be modulated by different miRNAs in various different types of cancer, including hepatocellular carcinoma (HCC), breast cancer, and GBM [ 115 , 116 ]. On the other hand, miR-296-3p is also downmodulated in GBM tissues compared to normal brain [ 117 ].…”
Section: Mirnas and Gliomasmentioning
confidence: 99%